Collaboration between midwives and dietitians in improving dietary intake of low SES women. (13th November 2019) - Super, S; Beulen, Y; Wagemakers, A
Abstract: Background: A healthy dietary intake during pregnancy is important for maternal and child health. However, pregnant women with a low socioeconomic status (SES) are less likely to adhere to nutrition guidelines as compared to high SES groups. Midwives in the Netherlands experience limited opportunities to provide nutrition advice. Dietitians could play a role in providing nutrition advice to pregnant women, but collaborations between midwives and dietitians are limited. Therefore, this study aimed to investigate the opportunities and barriers for collaboration between midwives and dietitians in antenatal care for low SES women. Methods: Questionnaires were administered amongst 134 dietitians to examine experiences of providing nutritional advice to pregnant women. Four focus groups were organised with midwives (2x) and dietitians (2x) to explore opportunities and barriers for collaboration. Results: Questionnaire results indicated that 73% of the dietitians like to see pregnant women more often in their practices and 78% feels the necessity to strengthen the collaboration with midwives. The focus groups showed that dietitians and midwives wish to strengthen the collaboration, but they also experience barriers: a focus on food risks rather than healthy nutrition in antenatal care, lack of referral procedures for women without medical necessity to see a dietitian, negative connotations with referring women to dietitians, and lack of time to discuss nutrition in consults by midwives. Conclusions: Midwives and dietitians recognise the importance of strengthening collaborations, but in order to do so, several challenges need to be overcome. In a follow-up of this study, pressure cooker sessions will be conducted to design an integral strategy in antenatal care to empower women to improve dietary intake. Key messages: There is a great potential to strengthen collaborations between midwives and dietitians in antenatal care to empower low SES pregnant women to improve dietary intake. Several barriers need to be overcome to design in an integral strategy in antenatal care to improve the dietary intake of low SES prengant women.